Histomorphometric effects of an antiretroviral treatment and obesity on the pancreas, liver, kidney and perivascular adipose tissue in a rat model - Nel, Simoné (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017